Comparison Of Antropometri And Physical Abilities Between Trained And Untrained Individuals In Second Growth Phase - Idzam Kholid Akbar, - (Fakultas Kedokteran, Universitas Airlangga, 2019)
The growth and development of the body goes through two phases of rapid growth. First phase (0-5 years) and second phase (10-17 years). This study aimed to compare anthropometry and physical abilities between trained and untrained individuals in the second rapid growth phase (adolescence). This research method used analytic observational with cross sectional design. The sample study used adolescents aged 14 years old, consisted of trained adolescent groups (n=25) and untrained adolescent groups (n=32), with categorized throught the International Physical Activity Questionnaires (IPAQ). Each group measured height, weight, chest circumference, vital lung capacity (VC), oxygen saturation (SpO2), heart rate resting, heart rate exercise, and VO2Max. The results of the different test between trained and untrained groups with a significance level of p<0.05 showed there were significant differences in body height (p=0.000), VC (p=0.000), SpO2 (p=0,001), heart rate rest (p=0.000), and VO2Max (p=0.000). There were no significant differences in body weight (p=0.053), chest circumference (p=0.226), and heart rate exercise (p=0.242). As a conclusion, anthropometry and physical abilities of trained individuals was greater than the untrained individuals in the second rapid growth phase (adolescence).